2019
DOI: 10.21037/sci.2019.08.06
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of umbilical cord mesenchymal stem cells using human blood derivatives accompanied with explant method

Abstract: Background: Mesenchymal stem cells (MSCs) are multipotent cells which can be isolated from many sources including umbilical cord. Isolation protocols are depended on either explant or enzymatic methods. Although fetal bovine serum (FBS) is used as a supplement in isolation and expansion of MSCs, human blood derivatives such as cord blood serum (CBS) and platelet lysate (PL) are attractive substitutes of FBS which overcome impediments of using FBS in clinical setups. Methods: Here we compared the effect of usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Mesenchymal Stromal Cells (MSCs) are non-hematopoietic multipotent cells which can be isolated from different tissues from adult, perinatal and fetal samples [1,2]. Some sources are adipose tissue [3], bone marrow [4], umbilical cord Wharton's jelly and blood [5,6], periosteum [7], skin [8], amniotic fluid [9] and the placenta [10]. These cells have the capability to differentiate into a variety of different mesenchymal lineage cells such as osteoblasts, chondrocytes, adipocytes, fibroblasts and myoblasts [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal Stromal Cells (MSCs) are non-hematopoietic multipotent cells which can be isolated from different tissues from adult, perinatal and fetal samples [1,2]. Some sources are adipose tissue [3], bone marrow [4], umbilical cord Wharton's jelly and blood [5,6], periosteum [7], skin [8], amniotic fluid [9] and the placenta [10]. These cells have the capability to differentiate into a variety of different mesenchymal lineage cells such as osteoblasts, chondrocytes, adipocytes, fibroblasts and myoblasts [2].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the DT for cells grown in XM remained steady and slowly increased from 15 h at P3 to 27 h at P40. Several published studies showed a signi cant increase in DT of adult and umbilical cord-derived MSCs upon passaging in FM compared to XM (20)(21)(22). In addition, the CFE of pMSCs was signi cantly lower in FM compared to XM.…”
Section: Discussionmentioning
confidence: 96%
“…Several reports describe xeno-free medium (XM) used to culture MSCs (15)(16)(17)(18)(19). The XM shows more promise in maintaining the selfrenewability of MSCs than FM (20)(21)(22). Despite the problems with maintaining MSCs during propagation, molecular changes limiting the self-renewal and differentiation potential upon passaging or culturing are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In response to these challenges, xeno-free medium (XM) has emerged as a promising alternative for MSC culture [ 17 21 ]. XM comprises human serum and proteins, offering potential advantages in maintaining MSC self-renewal [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%